Socioeconomic and environmental impact of urban agriculture practices in the Klang Valley, Malaysia - Abdul Hadi, Ahmad Hanis Izani (2018)
Rapid urbanization processes coupled with increased in urban population create social, environmental and economic problems worldwide. In general, it is estimated that 60 to 85% of human beings will be living in urban areas in 2025. The same urbanization process is occurring in Malaysia, where the urban population is predicted to be at 75 percent by 2020. As a result, greater pressures will be felt by city authorities especially in terms of competition of land for various urban functions, environmental degradation from pollutions as well as food security problems. The two most common unwanted consequences that are stemmed from increases in urban population are in terms of socioeconomic and environmental problems. Socioeconomic problems include urban poverty, food security, competition for land use, and other societal problems. In fact, urbanization process is also correspondingly linked with a wide range of other unwanted consequences in terms of environmental aspects such as resource scarcity, environmental degradation and climatic change and pollutions. To lessen both socioeconomic and environmental degradation problems, urban agriculture has been identified as one of sustainable tools that could be applied. Although urban agriculture will gain in recognition for its positive impacts on the urban society, its current practices in Malaysia is relatively low as compared to other countries. This could be stemmed from underestimated values of urban agriculture practices. This study is therefore conducted to assess the socioeconomic and environmental impact of urban agriculture practices in the Klang Valley, Malaysia. The first objective of the study is to identify the influential dimensions that shape perceptions on urban agriculture practices. A total of 875 respondents were interviewed across the Klang Valley areas using random sampling method. Exploratory Factor Analysis (EFA) method was utilized to analyze the data. The study results found that there are six influential dimensions that shape perception towards urban agriculture practices namely (1) social and health impact; (2) quantity and quality; (3) environmental impact; (4) economic impact; (5) diet preferences and (6) land use. Further analyses were conducted to distinguish the study results by category of respondents. The whole sample of the study was divided into two namely urban agriculture practitioners (n=297) and non-urban agriculture practitioners (n=578). In the case of urban agriculture practitioners, their perception towards urban agriculture practices are shaped by seven important factors namely (1) environmental impact; (2) economic impact; (3) social and health impact; (4) diet preferences; (5) food utilization; (6) land utilization; and (7) food safety. Meanwhile, for non-urban agriculture practitioners, eight influential factors were successfully identified. They were (1) social and health impact; (2) food safety; (3) environmental impact; (4) economic impact; (5) food utilization; (6) diet preferences; (7) food access; and (8) land utilization. To accomplish both second and third objectives of the study, choice experiment (CE) was utilized to estimate socioeconomic and environmental impact of urban agriculture practices. Respondents were asked to evaluate urban agriculture scenarios, which are described in terms of a set of attribute levels. Five most important attributes have been utilized for socioeconomic function namely food bills reductions; land use; knowledge and skills; social interactions; and price. In the case of environmental function, five selected attributes were food safety; landscaping; carbon footprint; waste management; and price. Each attribute comprises of at least two levels, where the lowest level was considered as a base line, while level two or three imply medium or high level of each attribute, respectively. The multinomial logit models were developed to obtain marginal value and compensating surplus of respondents to both functions. Based on study results, using the lowest attribute levels as dummy variables, all attribute levels obtained positive sign indicate that respondents prefer those levels more as compared to the base status quo used in the study. In the case of socioeconomic function, preferred attribute levels include reduction in food bill; land is fully utilized; exposure on knowledge and skills; and sharing knowledge. Meanwhile, for environmental function, preferred attribute levels include food safety; organic; greenery areas; less carbon footprint; and reuse and recycle. The results of the study also indicated that respondents were willing to pay more for improvements in urban agriculture scenarios as compared to the status quo, regardless whether they are urban agriculture practitioners or non-practitioners. Demographic profiles of respondents also played significant role in determining preferences for urban agriculture scenarios. Some of significant demographic variables include age group; ethnic; type of house; and income group of respondents. Aggregate values of urban agriculture practices were also calculated to accomplish the fourth objective of the study. In the case of socioeconomic impact, this activity is worth at RM10.15 million, considering 20% involvement from Klang Valley residents at the time. Using the same scenario, the value of environmental impact owing to urban agriculture practices was estimated at RM10.08 million. Due to its ability to contribute to both socioeconomic and environmental aspects, urban agriculture is worth to be promoted extensively in Malaysia. Policy makers should consider a number of approaches, especially in designing the promotional strategies to boost urban agriculture participation in order to make this activity socially, economically and environmentally worthwhile.